The quest for the golden fleas - Boyer, Crispin (Boyer, Crispin. Zeus the Mighty., 2019)
Zeus, a tiny hamster who believes he is the king of the gods, must find the legendary "Golden Fleas" and solidify his position before the other animals at Mount Olympus Pet Center rebel.